Risk factors of ovarian cancer: family history, obesity and oral contraceptive use - Kuchnicka, Aleksandra Amalia; Zielińska, Martyna; Zarankiewicz, Natalia; Kosz, Katarzyna; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2020)
<p class="Paragraph SCXW165926682 BCX2" style="font-weight: normal; font-style: normal; vertical-align: baseline; background-color: transparent; color: windowtext; text-align: justify; margin-left: 0px; margin-right: 0px; padding-left: 0px; padding-right: 0px; text-indent: 0px;"><span class="TextRun SCXW165926682 BCX2" style="font-weight: bold; font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 19.425px;" lang="EN-US" data-contrast="auto">Introduction and purpose:<span class="TextRun SCXW165926682 BCX2" style="font-weight: bold; font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 19.425px;" lang="EN-US" data-contrast="auto"> <span class="EOP SCXW165926682 BCX2" style="font-size: 12pt; line-height: 19.425px; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif;" data-ccp-props="{"134233117":true,"134233118":true,"335551550":6,"335551620":6}"> <p class="Paragraph SCXW165926682 BCX2" style="font-weight: normal; font-style: normal; vertical-align: baseline; background-color: transparent; color: windowtext; text-align: justify; margin-left: 0px; margin-right: 0px; padding-left: 0px; padding-right: 0px; text-indent: 0px;"><span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto">Ovarian cancer (OC) takes the 7th place among most common female malignancies worldwide. There are almost 240 <span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto">thousand<span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto"> of new cases diagnosed each year and the number is constantly growing. Defining risk factors of OC is essential to provide good education among women and predict this malignancy better. <span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto">The aim of this review is to analyze the current data <span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto">on<span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto"> risk factors<span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto"> of <span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto">OC concentrating on<span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto"> family history, obesity <span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto">and<span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto">oral <span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto">contraceptive<span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto">s<span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto"> use. <span class="EOP SCXW165926682 BCX2" style="font-size: 12pt; line-height: 27px; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif;" data-ccp-props="{"134233117":true,"134233118":true,"335551550":6,"335551620":6,"335559740":360}"> <p class="Paragraph SCXW165926682 BCX2" style="font-weight: normal; font-style: normal; vertical-align: baseline; background-color: transparent; color: windowtext; text-align: justify; margin-left: 0px; margin-right: 0px; padding-left: 0px; padding-right: 0px; text-indent: 0px;"><span class="TextRun SCXW165926682 BCX2" style="font-weight: bold; font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto">Material and method:<span class="EOP SCXW165926682 BCX2" style="font-size: 12pt; line-height: 27px; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif;" data-ccp-props="{"134233117":true,"134233118":true,"335551550":6,"335551620":6,"335559740":360}"> <p class="Paragraph SCXW165926682 BCX2" style="font-weight: normal; font-style: normal; vertical-align: baseline; background-color: transparent; color: windowtext; text-align: justify; margin-left: 0px; margin-right: 0px; padding-left: 0px; padding-right: 0px; text-indent: 0px;"><span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto">This review was based on articles <span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto">from 2010 to 2020 <span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto">collected in PubMed and <span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto">concerning the impact of several risk factors on developing OC.<span class="EOP SCXW165926682 BCX2" style="font-size: 12pt; line-height: 27px; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif;" data-ccp-props="{"134233117":true,"134233118":true,"335551550":6,"335551620":6,"335559740":360}"> <p class="Paragraph SCXW165926682 BCX2" style="font-weight: normal; font-style: normal; vertical-align: baseline; background-color: transparent; color: windowtext; text-align: justify; margin-left: 0px; margin-right: 0px; padding-left: 0px; padding-right: 0px; text-indent: 0px;"><span class="TextRun SCXW165926682 BCX2" style="font-weight: bold; font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto">Results:<span class="EOP SCXW165926682 BCX2" style="font-size: 12pt; line-height: 27px; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif;" data-ccp-props="{"134233117":true,"134233118":true,"335551550":6,"335551620":6,"335559740":360}"> <p class="Paragraph SCXW165926682 BCX2" style="font-weight: normal; font-style: normal; vertical-align: baseline; background-color: transparent; color: windowtext; text-align: justify; margin-left: 0px; margin-right: 0px; padding-left: 0px; padding-right: 0px; text-indent: 0px;"><span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto">The best described risk factor of OC is genetics and family history. 75% or hereditary OCs are associated to BRCA genes mutations, especially BRCA1. Other mutations increasing the risk of OC are MSH2 and MLH1 genes mutations. Diverse risk factors correlate with different histological subtypes of OC. Obesity increases the levels of estrogens, androgens and leptin, which may promote the proliferation of ovarian epithelial cells. Using oral contraceptives is related to 20% decreased risk of OC for each 5 years of use.<span class="EOP SCXW165926682 BCX2" style="font-size: 12pt; line-height: 27px; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif;" data-ccp-props="{"134233117":true,"134233118":true,"335551550":6,"335551620":6,"335559740":360}"> <p class="Paragraph SCXW165926682 BCX2" style="font-weight: normal; font-style: normal; vertical-align: baseline; background-color: transparent; color: windowtext; text-align: justify; margin-left: 0px; margin-right: 0px; padding-left: 0px; padding-right: 0px; text-indent: 0px;"><span class="TextRun SCXW165926682 BCX2" style="font-weight: bold; font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto">Conclusions:<span class="TextRun SCXW165926682 BCX2" style="font-weight: bold; font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto"> <span class="EOP SCXW165926682 BCX2" style="font-size: 12pt; line-height: 27px; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif;" data-ccp-props="{"134233117":true,"134233118":true,"335551550":6,"335551620":6,"335559740":360}"> <p class="Paragraph SCXW165926682 BCX2" style="font-weight: normal; font-style: normal; vertical-align: baseline; background-color: transparent; color: windowtext; text-align: justify; margin-left: 0px; margin-right: 0px; padding-left: 0px; padding-right: 0px; text-indent: 0px;"><span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto">BRCA1/2, MSH2 and MLH1 mutations and obesity are well-defined risk factors of ovarian cancer. The first-choice risk-reducing procedure among BRCA carriers is bilateral <span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto">salpingo<span class="TextRun SCXW165926682 BCX2" style="font-size: 12pt; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif; line-height: 27px;" lang="EN-US" data-contrast="auto">-oophorectomy. On the contrary, using oral contraceptives results in decreased risk of OC. Promoting knowledge about OC risk factors among women and healthcare professionals is crucial in order to reduce the number of ovarian cancer.<span class="EOP SCXW165926682 BCX2" style="font-size: 12pt; line-height: 27px; font-family: Times New Roman, Times New Roman_EmbeddedFont, Times New Roman_MSFontService, serif;" data-ccp-props="{"134233117":true,"134233118":true,"335551550":6,"335551620":6,"335559740":360}">